A single night time dose of ranitidine in the acute treatment of gastric ulcer: a European multicentre trial. Issue 7 (July 1986) - Ryan, F P; Jorde, R; Ehsanullah, R S; Summers, K; Wood, J R
Abstract : Four hundred and twenty eight patients with endoscopically diagnosed gastric ulcers, randomly allocated to treatment with ranitidine 300 mg at night or ranitidine 150 mg twice daily, were evaluated in a double blind multicentre trial conducted in 10 European countries. After four weeks, complete ulcer healing was observed in 138 of 211 patients (65%) treated with ranitidine 300 mg nocte and in 155 of 217 patients (71%) receiving 150 mg bd. Cumulative healing rates at eight weeks were 90% and 93%, respectively. There was no statistically significant difference between the healing rates at either four or eight weeks. The treatment regimens were equally effective at rapidly reducing the incidence of ulcer related symptoms. Adverse events reported were minor and equally distributed between the two groups. The results of this trial show that 300 mg of ranitidine administered at night is an effective and safe alternative to the current twice daily regimen for the short term treatment of gastric ulcer.